Belgium : 2008 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2008)
Although economic performance has remained good, difficulties in building consensus for institutional reform have caused an ill-affordable hiatus in economic policymaking. Robust economic activity absorbed a growing labor force and allowed the unemployment rate to decline continuously. Low-income groups are being disproportionately affected by the food and energy price increases, triggering a necessary increase in targeted income support. The authorities agreed that various indicators suggest that the current level of the real effective exchange rate is broadly appropriate.